Focus stacking from a purely geometrical point of view - Glaeser, Georg (Array, 2019)
In order to create extremely sharp photographs, focus stacking has become a widely used method nowadays, mainly in macro or micro photography. Whereas the aspect of computationally detecting sharp regions of an image has been dealt with in many publications, there is only little published about the geometric background. This paper analyzes the process from a purely geometrical point of view, revealing some non-trivial aspects that may potentially also lead to improvements in a variety of applications such as the 3D scanning of small objects. It is shown that - under calibrated conditions and with certain restrictions - focus stacking of a scene leads to arbitrarily many geometrically correct perspective images of this scene, even including normal projections. The reason for this is that the process of photography never leads to purely two-dimensional images, but collinearly distorted spatial images.